Gut microbiota is involved in the exacerbation of adrenal glucocorticoid steroidogenesis in diabetic animals by activation of the TLR4 pathway - Magalhães, Nathalia Santos; Chaves, Amanda Silva; Thomasi, Beatriz; Insuela, Daniella Bianchi Reis; Pauer, Heidi; Rêgo, Amanda Mendes; Hardoim, Cristiane Cassiolato Pires; Antunes, Luis Caetano Martha; e Silva, Patrícia Machado Rodrigues; Martins, Marco Aurélio; Carvalho, Vinicius Frias (Frontiers in Endocrinology, 2025)
IntroductionDiabetes induces glucocorticoid production in patients and animal models, however, the exact mechanism behind this phenomenon is still elusive. The activation of toll-like receptor (TLR) 4 induces glucocorticoid production by the adrenals. Since diabetic patients showed gut dysbiosis in parallel to an increase in epithelial-intestinal permeability, this study investigates the role of TLR4 activation by gut bacteria-derived lipopolysaccharide on the overproduction of corticosterone in diabetic rodents.MethodsDiabetes induction was achieved through the intravenous injection of alloxan, followed by treatments with antibiotic therapy or TLR4 antagonist (TAK-242) for 14 consecutive days.ResultsDiabetic animals showed an increase in plasma corticosterone levels as well as overexpression of TLR4 and Toll/IL-1R domain-containing adaptor-inducing IFN-β (TRIF) in the adrenals. Diabetic mice also showed gut dysbiosis, with an increase in the relative proportion of potentially pathogenic bacteria. We observed morphological alterations as well as increased inflammation in the colon with a predominance of a Th17 cytokine profile in diabetic mice, in parallel to an increase in the epithelial-intestinal permeability and lipopolysaccharide content in the adrenals. TAK-242 significantly decreased the overexpression of adrenocorticotropic hormone receptor and 11β-hydroxysteroid dehydrogenase type 1 in the adrenal glands of diabetic mice. Furthermore, both TLR4 antagonist and TLR4 mutant mice (C3H/HeJ) induced a significant reduction in plasma corticosterone levels in diabetic mice.ConclusionOur findings revealed that gut dysbiosis participates in the exacerbation of corticosterone production by diabetic animals, suggesting that therapeutic strategies that can normalize gut microbiota in diabetics represent promising therapeutic candidates for the treatment of glucocorticoid-induced comorbidities in diabetes.